Faktor Yang Mempengaruhi E-Trust Serta Dampaknya Pada Repurchase Intention - luluk tataningtyas; Endang Tjahjaningsih (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The existence of the internet creates a new paradigm in word of mouth communication, the phenomenon of e-wom is considered an evolution from traditional interpersonal communication to a new generation. In a study conducted by Meybiani et al., (2019), the results showed that the e-WOM variable had no significant effect on consumer buying interest, while Lita & Auliya (2019) gave the result that online reviews had no significant effect on repurchase intentions, trust in consumers. web has a significant effect on repurchase intentions, online transaction security has a significant effect on repurchase intentions, privacy has a significant effect on repurchase intentions. Meanwhile, in a study conducted by Sari (2021), it was explained that E-WOM had a significant positive effect on repurchase intention. The purpose of this study is to analyze and explain the effect of online shopping experience and the effect of e-wom on repurchase intentions through e-trust. This study uses an explanatory research type, which tries to explain the relationship between the variables contained in the study. The variables in this study are online shopping experience, E-Wom, e-trust and repurchase intention. The minimum sample used is 89 respondents, the researchers will take a sample of 100 respondents. The Adjusted R² value of 0.295 means that the influence of the online shopping experience variable (X1) and the e-wom variable (X2) can explain the variation of changes in the e-trust variable (Y1) of 29.5%, the Adjusted R² value of 0.369 means the magnitude of the online influence shopping experience (X1), e-wom (X2) and e-trust (Y1) variables on repurchase intention (Y2) by 36.9%